Predation in the reindeer husbandry area in Finland during 1976-86 - Nieminen, Mauri; Leppäluoto, Juhani (Rangifer, 1988)
During the years 1976-86 predators killed a total of 11 295 reindeer in the Finnish reindeer husbandry area. Predators killed mostly calves and hinds. With the exception of the Kåsivarsi and Muotkatun-turi reindeer herding cooperatives, kills of predators were concentrated in the reindeer herding areas on the eastern border. During 1976-86 predators killed most reindeer in April - June, and the majority of preys were calves. Most reindeer were killed by wolves (26.9%), bears (24.7%), wolverines (22.6%) and eagles (15.9%). Wolves, bears, wolverines and lynxes killed mainly adult reindeer, eagles killed mainly calves. Wolves killed reindeer mainly during October - January, lynxes during January - April, wolverines during February - April, eagles during May - July and bears during May - October. During the last years the number of reindeer killed by lynxes has increased in Finland. Petovahingot Suomen poronhoitoalueella vuosina 1976-86. Abstract in Finnish / Yhteenveto: Viimeisen kymmenen vuoden aikana porojen måårå on lisååntynyt suuresti Suomessa. Vuosina 1976-86 pedot tappoivat Suomen poronhoitoalueella yhteenså 11 295 poroa. Pedot tappoivat pååasiassa vasoja ja vaatimia. Käsivarren ja Muotkatunturin paliskuntia lukuunottamatta petovahingot kohdistuivat lhinn poronhoitoalueen itrajalla oleviin paliskuntiin. Vuosina 1976-86 pedot tappoivat poroja eniten huhti-kesåkuun aikana. Eniten pedot tappoivat tuolloin vasoja. Eniten poroja tappoivat sudet (26.9%), karhut (24.7%), ahmat (22.6%) ja kotkat (15.9%). Sudet, karhut, ahmat ja ilvekset tappoivat pååasiassa aikuisia poroja, kotkat vasoja. Sudet tappoivat poroja låhinnå loka-tammikuussa, ilvekset tammi-huhtikuussa, ahmat helmi-heinåkuussa ja karhut touko-lokakuussa. Viime vuosina ilvesten tappamien porojen måårå on kas vanut Suomessa. Rovdjursskador inom det finska renskotselsområdet under åren 1976-86. Abstract in Swedish / Sammandrag: Under de senaste tio åren har antalet tamrenar ökat betydligt i Finland. Under åren 1976-86 dodade rovdjur totalt 11 295 renar i finska renskotselområdet. Kalvar och vajor utgjorde huvuddelen av dessa. Med undantag av Kåsivarsi och Muotkatunturi renbeteslag, var rovdjursrivningarna konsentrerade i renbeteslagen nårmast ostra grånsen. Under åren 1976-86 blev de fiesta renar rivna i april-juni. Av dessa var det flest kalvar. Varg tog flest renar (26,9%), bjorn 24,7%, jårv 22,6%, och orn 15,9%. Varg, bjorn, jårv och lo dodade mestadels vuxna renar, medan orn i huvudsak tog kalvar. Varg dodade ren våsentligen i månaderna oktober-januari, lo i januari-april, jårv i februari-april, orn i mai-juli och bjorn genom må-naderna mai-oktober. De senaste åren har antalet renar rivna av lodjur okat i Finland.